Chlorella vulgaris is an effective supplement in counteracting non‐alcoholic fatty liver disease‐related complications through modulation of dyslipidemia, insulin resistance, and inflammatory pathways. Issue 10 (30th August 2021) - Moradi, Mohamad‐nabi; Behrouj, Hamid; Alipoor, Behnam; Kheiripour, Nejat; Ghasemi, Hadi; Ghasemi, Hassan
Abstract: This study was aimed to investigate the effect of microalgae Chlorella vulgaris ( C. vulgaris ) on nonalcoholic fatty liver disease (NAFLD)‐related complications induced by high‐fat diet (HFD). Fifty adult male rats were divided into six groups. Control group and HFD group treated with or without C. vulgaris 5% and 10%. Biochemical parameters in serum were measured by spectrophotometric and enzyme‐linked immunosorbent assay (ELISA) methods. The relative gene expression levels of Tumor Necrosis Factor‐alpha (TNF‐α), NF‐kappa B (NF‐ƙB), and p38 Mitogen‐Activated Protein Kinases (p38 MAPK) in the liver were assessed by using quantitative real‐time PCR, while the protein levels of NF‐ƙB and TNF‐α in the liver homogenate were determined by ELISA. The effects of HFD significantly were reversed by C. vulgaris, especially at a 10% dose. Therefore, it can be concluded that C. vulgaris therapeutically could be useful to improve NAFLD and its complications. Practical applications: It is established that NAFLD is associated with the resistance to insulin, dyslipidemia, and inflammation. Accordingly, modulating of these conditions may be useful in the management of NAFLD. Our results showed the effectiveness of C. vulgaris against NAFLD‐related complication through the alleviating insulin resistance, dyslipidemia and also down‐regulation of inflammatory genes in p38 MAPK/TNF‐α/NF‐ƙB pathway. The results of our study may be useful for scientist to prepare an effective supplement from C. vulgaris to overcoming NAFLD‐related complications. Abstract : Schematic representation of the effect of C. vulgaris against NAFLD‐related complications. Administration of C. vulgaris especially at a 10% dose, significantly modulated HFD‐induced phenotypes including; insulin resistance, dyslipidemia and inflammatory pathways.